2005
DOI: 10.1021/ma0518961
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Thermal and Elastic Properties of the Interlamellar Phase of Semicrystalline Polyethylene by Molecular Simulation

Abstract: We present the first theoretical estimates for thermoelastic properties of the noncrystalline domain (the "interlamellar phase") of semicrystalline polyethylene obtained by Monte Carlo simulations. The interlamellar phase is prescribed to be thermodynamically metastable, with the constraints that it have an average density less than that of the crystal and that it be bounded by two static crystalline lamellae oriented with the {201} crystal plane parallel to the interface. Polyethylene was modeled using a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 33 publications
5
82
2
Order By: Relevance
“…Adhesion is fairly independent of the fiber diameter for Nylon 6, contrasting other fibers that show an increasing adhesion for smaller diameters. [21][22][23] To ensure consistency, another nano-cheese-cutter was prepared on yet another AFM cantilever. Figure 4(a) shows the loading-unloading cycles in the same two fibers.…”
Section: Mechanical Characterization and Adhesion Measurementmentioning
confidence: 99%
“…Adhesion is fairly independent of the fiber diameter for Nylon 6, contrasting other fibers that show an increasing adhesion for smaller diameters. [21][22][23] To ensure consistency, another nano-cheese-cutter was prepared on yet another AFM cantilever. Figure 4(a) shows the loading-unloading cycles in the same two fibers.…”
Section: Mechanical Characterization and Adhesion Measurementmentioning
confidence: 99%
“…In this study, two independent micromechanical homogenization approaches are tailored to extract the interphase stiffness from that of the interlamellar domain. Then, they are applied to the Monte Carlo (MC) molecular simulation results by in 't Veld et al who reported the variation of the interlamellar stiffness components, boldCij il , with temperature in the range of 350–450 K. The reader is referred to the original article for the details of the molecular simulation. However, for the purposes of this study, it is worth noting that the simulations employed a well‐validated united atom force field for PE and an MC algorithm to equilibrate the ensemble of configurations with respect to interatomic packing interactions, intramolecular conformational degrees of freedom, and connectivity between the interlamellar phase and the neighboring crystalline lattices.…”
Section: Introductionmentioning
confidence: 99%
“…The stable timestep of the CG models was determined as the largest timestep for which the drift of total energy in a 1 ps NVE simulation was less than 1% of the average kinetic energy. The united atom simulation was performed using the potentials of In't Veld et al Due to the reduced degrees of freedom and increased stable timestep, the HB and NLB models are two orders of magnitude faster than the atomistic simulations and nearly three times as fast as the UAM model.…”
Section: Methodsmentioning
confidence: 99%